Modern Approaches for Detection of Glanders and Melioidosis. Identification and Typing of Burkholderia mallei and Burkholderia pseudomallei - V. A. Antonov; V. I. Ilyukhin; N. P. Khrapova; E. V. Prokhvatilova; D. V. Viktorov; T. V. Senina; A. A. Budchenko; G. A. Tkachenko; V. V. Alekseeva; I. B. Zakharova; S. S. Savchenko; O. V. Zinchenko; et al. (Проблемы особо опасных инфекций, 2012)
Analysed are the methodological approaches used for identification and typing of B. mallei and B. pseudomallei. Suggested are recommendations for improvements of algorithms of laboratory diagnosis of glanders and melioidosis including wide range of biochemical, immunodiagnostic and molecular genetic methods.